A three-coloured Europe: European flags seeking to break away from the past - González Fernández, José Luis; Orobon, Marie-Angèle (Historia y Comunicación Social, 2023)
This article attempts to record the spread and influence of the French tricolour flag throughout Europe, particularly Germany, Spain, and to a lesser extent Italy, from the era of revolutions at the end of the 18th century to the interwar period of the 20th century. The analysis focuses on how these countries invented or chose chromatic triads with which they cemented their national identity; a process which did not go without clashes or without a wish to break away from what preceded. Beyond the historical and political reach of the French emblem, the objective of this text is to offer a reflection on the symbolic potential of flags and colours in contemporary Europe.